Contamination Potentials of Household Water Handling and Storage Practices in Kirundo Subcounty, Kisoro District, Uganda - Alexander, Agensi; Julius, Tibyangye; Andrew, Tamale; Ezera, Agwu; Christine, Amongi (Hindawi Journal of Environmental and Public Health, 2019)
Waterborne diseases constitute a major public health burden in developing and underdeveloped countries. Consumption of contaminated water causes health risk to the public, and the situation is alarming in rural areas. *e objective of this study was to assess the contamination potentials of different house water handling and storage practices in the Kirundo subcounty, Kisoro District, Uganda. Material and Methods. A cross-sectional and descriptive study in which 344 water samples were collected randomly and analysed for bacteriological contamination, total coliforms (TCs) and Escherichia coli per 100 ml, using the Most Probable Number (MPN) technique and reported in terms of CFU/100 ml. Results. *e 43.2% samples from unprotected water sources had total coliforms and 34.1% had Escherichia coli. In analysed household drinking water, 25% had total coliforms and 8.7% had Escherichia coli. Most drinking water sources were found to have coliform counts above the recommended national and international guidelines. *ere was a statistically significant difference among water sources with respect to total coliforms and Escherichia coli (p < 0.05). Conclusion. *e overall results indicated that there is a strong linkage between microbiological water quality and water source sanitation; hence, the protected water source was safer than unprotected water sources. For the unprotected water sources, protection strategies as well as monitoring are recommended for this community.